Assessment of toxicity and mechanism of the drug (camphoric acid derivative) effect on the organism (Environment & Health, 2022)
The drugs, their active ingredients under conditions of manufacture and pharmaceutical waste at the ingress in the environment can be hazardous to the human health. The toxicological examination enables to predict the risk of their adverse effects on the organism with a determination of the prior criteria of hazard.Objectives: We defined the probable toxic effects and the mechanism of their formation under various conditions of the exposure of the original anti-diabetic drug based on a camphoric acid derivative (Diacamph - DCMPh) under various conditions of its exposure.Methods: The peculiarities of DCMPh effect on the organism were studied in the acute, sub-acute, and chronic experiments under different conditions of the drug introduction to animals by the indicators characterizing a state of the organism in a whole and the separate organs and systems of the organism and individual organs and systems, including prooxidant- antioxidant and immune systems. Its possible allergenic and mutagenic effects were studied in a separate run of the experiments.Results: Our studies showed that DCMPh is virtually non-toxic in terms of an acute toxicity, does not accumulate, has no local irritant, mutagenic and allergenic effects, but is capable of the skin resorption. Adverse effect of DCMPh on the organism under its oral and inhalation introduction are realized through the disturbance of the prooxidant-antioxidant balance and cellular components of the immunological resistance. We determined a high sensitivity of lungs to the inhalation impact of DCMPh, taking into account an increase of the free radical oxidation in the organ tissue on the background of the weakening of the antioxidant system and a decrease of the functional reserve of neutrophils manifested in the aftereffect period. The high sensitivity of the lungs to the inhalation effect of DCMPh was determined taking into account the increase in free radical oxidation in the organ tissue on the background of the weakening of the antioxidant system and the decrease in the functional reserve of neutrophils, which manifests itself during the aftereffect period.Conclusions: Taking into account the mechanism of toxic action, the maximum permissible concentration of DCMPh in the air of the working area was substantiated at the level of 0.4 mg / m3, hazard class II.
Keywords: antidiabetic drug – camphoric acid derivative; toxicity; mechanism of toxic effect